Subtype distribution of blastocystis isolates in Sebha, Libya - Abdulsalam, A.M.; Ithoi, I.; Al-Mekhlafi, H.M.; Al-Mekhlafi, A.M.; Ahmed, A.; Surin, J. (Public Library of Science, 2013)
Blastocystis is a genetically diverse and a common intestinal parasite of humans with a controversial pathogenic potential. This study was carried out to identify the Blastocystis subtypes and their association with demographic and socioeconomic factors among outpatients living in Sebha city, Libya